(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
Prior to the watching brief taking place, areas of sensitivity were identified, largely based around the medieval core of the town. The potential was high, along with the possibility of resolving issues such as the existence of town walls, the location of the town market, and the primacy of either the High Street or Quality Street.